1999
DOI: 10.1097/00042560-199904150-00015
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk in Selenium-Deficient HIV-Positive Children

Abstract: In pediatric HIV-infection, low plasma level of selenium is an independent predictor of mortality, and appears to be associated with faster disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(85 citation statements)
references
References 20 publications
3
73
1
1
Order By: Relevance
“…b From generalized estimating equations using a working binomial distribution and a log link function. risk elevations are lower, however, than risk elevations reported in a US study among 24 HIV-infected children, in which low plasma selenium levels (r85 mg/l) were associated with a six-fold increased mortality risk (Campa et al, 1999). The fact that our study population was considerably younger at enrollment (median age 10.5 weeks vs 4.2 y in the US study) may partly account for the differences observed.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…b From generalized estimating equations using a working binomial distribution and a log link function. risk elevations are lower, however, than risk elevations reported in a US study among 24 HIV-infected children, in which low plasma selenium levels (r85 mg/l) were associated with a six-fold increased mortality risk (Campa et al, 1999). The fact that our study population was considerably younger at enrollment (median age 10.5 weeks vs 4.2 y in the US study) may partly account for the differences observed.…”
Section: Discussioncontrasting
confidence: 66%
“…Observational studies from the US among HIV-infected children suggest that low selenium levels are associated with impaired anthropometric and immunological status (Miller et al, 1993), faster HIV disease progression (Campa et al, 1999), and increased risk of mortality (Campa et al, 1999). However, it is not clear whether these findings apply to sub-Saharan Africa, the region most deeply afflicted with the AIDS epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…In HIV-infected children, low levels of plasma Se were significantly and independently related to mortality (RR 5.96, 95%CI 1.32-26.81; P = 0.02) and faster disease progression. 20 Se also appears to be protective in subjects infected with hepatitis-virus (B or C) against the progression of the condition to liver cancer (see section on Cancer). 21,22 It is notable that viruses may be capable of hijacking the Se supply of the host by incorporating Se into viral selenoproteins thereby reducing the ability of the host to mount an effective immune response.…”
Section: Viral Infectionmentioning
confidence: 99%
“…Yu et al (63) , Bjelakovic et al (64) In US patients with relatively low Se status (plasma Se < 85 mg/l) HIV infection progresses more rapidly to AIDS with higher mortality Baum et al (65) , Campa et al (66) In a Tanzanian observational study of 949 HIV-positive pregnant women mortality decreases with increase in plasma Se ( > 85 mg/l) over 5-year follow-up period Kupka et al (67) Cancer Inverse relationship between crop and human Se status and cancer incidence in North America…”
Section: Antiviral Effects and Hivmentioning
confidence: 99%